Sishen Pill and its active phytochemicals in treating inflammatory bowel disease and colon cancer: an overview - Zhang, Boxun; Cheng, Yingying; Jian, Qin; Xiang, Sirui; Xu, Qi; Wang, Chuchu; Yang, Chuan; Lin, Junzhi; Zheng, Chuan (Frontiers in Pharmacology, 2024)
The incidence of inflammatory bowel disease (IBD) and the associated risk of colon cancer are increasing globally. Traditional Chinese medicine (TCM) treatment has unique advantages. The Sishen Pill, a common Chinese patented drug used to treat abdominal pain and diarrhea, consists mainly of Psoraleae Fructus, Myristicae Semen, Euodiae Fructus, and Schisandra Chinensis. Modern research has confirmed that Sishen Pill and its active secondary metabolites, such as psoralen, myristicin, evodiamine, and schisandrin, can improve intestinal inflammation and exert antitumor pharmacological effects. Common mechanisms in treating IBD and colon cancer mainly include regulating inflammation-related signaling pathways such as nuclear factor-kappa B, mitogen-activated protein kinase, phosphatidylinositol 3-kinase, NOD-like receptor heat protein domain-related protein 3, and wingless-type MMTV integration site family; NF-E2-related factor 2 and hypoxia-inducible factor 1α to inhibit oxidative stress; mitochondrial autophagy and endoplasmic reticulum stress; intestinal immune cell differentiation and function through the Janus kinase/signal transducer and activator of transcription pathway; and improving the gut microbiota and intestinal barrier. Overall, existing evidence suggests the potential of the Sishen pill to improve IBD and suppress inflammation-to-cancer transformation. However, large-scale randomized controlled clinical studies and research on the safety of these clinical applications are urgently required.